MAKNA SIMBOLIK TRADISI PEMBERIAN BORAS SIPIR NI TONDI PADA ACARA PERNIKAHAN ADAT BATAK DI KOTA PEKANBARU - Fani Aprilia Napitupulu; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The tradition of giving Boras Sipir Ni Tondi is one of the traditions that exist in the Toba Batak people. In the tradition of giving Boras Sipir Ni Tondi, there are symbolic aspects that have certain meanings that are represented through tools or movements found in the tradition of giving Boras Sipir Ni Tondi. This study has a purpose, namely to find out the meaning of symbolic situations, the meaning of interaction products, and the meaning of interpretation of the tradition of giving Boras Sipir Ni Tondi in Pekanbaru city. This study uses a qualitative research method with a symbolic interaction approach. There were 18 informants in this study, namely Raja Parhata (3 people), male parents (3 couples), female parents (3 couples), Hula-hula (3 people), brides (3 couples), and the community/invited guests (3 people) were selected purposively with several predetermined criteria. Data collection techniques used are through interviews, observation, and documentation. The results of this study indicate that the meaning of symbolic situations in the tradition of giving Boras Sipir Ni Tondi in Pekanbaru city consists of physical objects and social objects. Physical includes tandok, ulos, boras, jambar, money, and betel leaf. The social object is the movement of tortor panomu-nomuan, at first, tortor, tortor sitio- tio, and umpasa (prayer). The meaning of the social interaction product of the tradition of giving Boras Sipir Ni Tondi includes meaning from the side of Raja Parhata/customary leaders interpreting the tradition of giving Boras Sipir Ni Tondi this as a gift of blessing, from the bride's perspective interpreting it as a prayer and hope from parents and blessings received so that the bride and groom being able to run the new household well, from the parents' point of view it means giving prayers to their children so that they are always blessed and able to live a new household life well, from the Hula-hula (uncle) side it means to give blessings, prayers and hopes for the future. kindness and strong faith and a united soul in the household, as well as from the community side to give blessings and prayers to the bride and groom. The meaning of the interpretation of the tradition of giving Boras Sipir Ni Tondi includes open actions and closed actions which include internal and external motivations and feelings of the bride and groom, while open actions include facial expressions of the bride and groom. Keywords: Symbolic meaning, Situation symbolic, Social Interpretation , Product Social Interaction, Boras Sipir Ni Tondi.